1970
DOI: 10.1042/bj1180047
|View full text |Cite
|
Sign up to set email alerts
|

The fate of benzoic acid in various species

Abstract: 1. The urinary excretion of orally administered [(14)C]benzoic acid in man and 20 other species of animal was examined. 2. At a dose of 50mg/kg, benzoic acid was excreted by the rodents (rat, mouse, guinea pig, golden hamster, steppe lemming and gerbil), the rabbit, the cat and the capuchin monkey almost entirely as hippuric acid (95-100% of 24h excretion). 3. In man at a dose of 1mg/kg and the rhesus monkey at 20mg/kg benzoic acid was excreted entirely as hippuric acid. 4. At 50mg/kg benzoic acid was excreted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 199 publications
(97 citation statements)
references
References 6 publications
4
90
1
2
Order By: Relevance
“…It has been reported that a 2% solution of NaB in drinking water is safe for lifelong treatment in mice without any noticeable side effects (12). In accordance with the published reports (13,14), a minor amount of benzoic acid, a direct metabolite of cinnamic acid (15), is also excreted in the urine of humans.…”
Section: Ultiple Sclerosis (Ms)supporting
confidence: 71%
“…It has been reported that a 2% solution of NaB in drinking water is safe for lifelong treatment in mice without any noticeable side effects (12). In accordance with the published reports (13,14), a minor amount of benzoic acid, a direct metabolite of cinnamic acid (15), is also excreted in the urine of humans.…”
Section: Ultiple Sclerosis (Ms)supporting
confidence: 71%
“…The results of present experiment show the antibacterial effects of benzoic acid in broiler chickens, although lower bacterial counts in gastrointestinal digesta were not reflected in better performance of the birds. Bridges et al (1970) reported that the metabolic pathways of supplemented benzoic acid differ among mammalian species. Polonen et al (2000) studying the effect of benzoic acid in mink, blue fox and racoon have found species-specific differences in excreting of this compound among its effects on poultry is scarce.…”
Section: Discussionmentioning
confidence: 99%
“…4'-Hydroxyhippuric and hippuric acid were also present in urine collected from all the volunteers after raspberry intake with total 0-48 h excretion values of 16.1 ± 1.9 μmol, and 239 ± 55 μmol, respectively. Although hippuric acid, formed by hepatic glycination of benzoic acid, has been described as a common metabolite of many flavonoids [17], it was not included in the calculation of the percentage recovery because its high background levels, originating from other dietary and endogenous sources [18][19][20], make it difficult to determine the amounts derived from the metabolism of anthocyanins. Thus, the overall recovery of anthocyanins and their metabolites observed in this study was 43.9 ± 8.0 μmol which corresponds to 15.0% of anthocyanin intake ( Table 2).…”
Section: Excretion Of (Poly)phenol Metabolites In Urinementioning
confidence: 99%